HUBUNGAN ACADEMIC SELF EFFICACY DENGAN KEJADIAN ACADEMIC BURNOUT PADA MAHASISWA FARMASI - Putra, Andika Parnomo; Susanti, Indri Heri; Sumarni, Tri (Coping: Community of Publishing in Nursing; Vol 10 No 6 (2022): Desember 2022DO - 10.24843/coping.2022.v10.i06.p03, 2022)
Academic self efficacy is a paradigm of studying for students that is mostly believed to help them in managing time and studying environment effectively. The decreasing academic self efficacy in a student can cause an increasing academic burnout. Academic burnout is an exhaustion in a student caused by their study demands, and a feeling of incompetency as a student that can cause a stress and the other psychological factor. This research aims to know the relationship between academic self efficacy and academic burnout within students of Undergraduate Program of Pharmacy, Health Faculty in Harapan Bangsa University. This research using quantitative methods with a cross sectional approach. All pharmacy students were involved in this study as respondents. Sampling method used in this research is probability sampling proportionate stratified random sampling with 190 respondents. Research instruments used in this study are Academic Self Efficacy Scale and Maslach Burnout Inventory-Student Survey questionnaire. The result shows that academic self efficacy within pharmacy students were in medium level (62,1%) and academic burnout were in medium level as well (52,6%). The Spearman Rank test shows that there is relationship between academic self efficacy and academic burnout within pharmacy students with p value 0,000 (p<a).